y-Fe2O3 Nanoparticle modified electrode surface for monitoring gestational diabetes mellitus - Xia, Honghui; Liang, Juanjuan; Zhang, Na; Gopinath, Subash C B; Wu, Yuan Seng *; Wu, Ailing (American Scientific Publishers, 2023)
Gestational diabetes mellitus (GDM) is a medical complication during the pregnancy period, caused by the elevation of blood glucose. Adiposity, fetal growth, hypertensive disorders are highly associated with GDM. In addition, a longer-term health issues such as pre-diabetes, obesity, cardiovascular diseases are addressed with mothers having GDM. There is an effective diagnostic approach is mandatory for GDM and this research work developed a sensitive glucose biosensing on iron oxide nanoparticle (FeONP; γ -Fe 2 O 3 ) modified interdigitated aluminium electrode (IDE) with the substrate silicon followed by overlaying silica upon oxidation. Glucose oxidase (GOx) was immobilized on FeONP modified surface through amine and aldehyde linkers and then glucose was quantified. FeONP increases the attachment of GOx on IDE and optimized concentration of 200 nM GOx was desired on IDE to achieve a maximum current response with glucose and GOx interaction. The gradual increment in current was recorded by adding different glucose concentrations and the detection limit was calculated to be 10 mg/dL with an R ² value of 0.9903 (on a linear concentrations 10–640 mg//dL). Further, control experiment was failed to display the current response, specifying the genuine identification of glucose on FeONP attached IDE surface.